Etiology and characteristics of burn injuries in patients admitted at Burns Center, Civil Hospital Karachi - Muhammad Osama Anwer; Muhammad Uzair Abdul Rauf; Noorulain Chishti; Sanam Anwer (Wolters Kluwer Medknow Publications, 2016)
Background: Morbidity and mortality by burns are alarmingly high among the developing countries due to inadequate care facilities. Among these nations, Pakistan has one of the highest burn-related incidents. The dilemma is that most of these deaths and disabilities are curable and preventable. Therefore, there is an urgent need of creating an effective infrastructure to cut down these high number of cases. Methods: We conducted a cross-sectional study at Burns Center, Civil Hospital Karachi. Two hundred and seventy-five patients participated in the study. Data were analyzed using SPSS version 17.0. Results: Among these 275 patients interviewed 63.6% (n = 175) were males whereas 36.4% (n = 100) were females. The mean age of our participants was found to be 26.36 years. A large proportion of the population belonged to the urban areas, i.e. 76.4% (210), whereas only 23.6% (65) were from rural areas, with P = 0.001. About 63.6% of the burn injuries occurred at home (175) while 25.1% (69) got injured at the place of work. Most of the cases were found to be accidental 93.8% (258). About 53.1% (146) had <20% of the total body surface area effected, whereas 16.7% (46) had more than 40% burns. Conclusion: By introducing an effective awareness program regarding burns and teaching first aid techniques to general population, a high number of burn-related accidents could be prevented.